Microbiology of the Upper and Lower Airways in Pediatric Cystic Fibrosis Patients. (August 2017) - Sobin, Lindsay; Kawai, Kosuke; Irace, Alexandria L.; Gergin, Ozgul; Cunningham, Michael; Sawicki, Gregory S.; Adil, Eelam A.
Objective: To evaluate the microbiology of the upper and lower airways in pediatric cystic fibrosis (CF) patients who underwent sinus surgery. Study Design: Retrospective case series with chart review. Setting: Tertiary care children's hospital. Subjects and Methods: A total of 201 paired sinus and pulmonary cultures from 105 CF patients were identified between 1996 and 2014. Demographics and culture results were analyzed. Results: The mean age of patients was 11.2 ± 5.4 years (range, 1-27 years), and approximately one-half were female. Methicillin-sensitive Staphylococcus aureus was the most common pathogen overall. A significantly higher prevalence of Pseudomonas aeruginosa (32% for pulmonary and 37% for sinus cultures) was observed in older patients versus younger patients ( P < .001). There was low to moderate agreement between sinus and pulmonary cultures (Kappa statistic range, 0.03-0.56). The prevalence of methicillin-resistant S aureus (MRSA) increased significantly for lower respiratory tract culture (from 5% to 16%) and sinus culture (from 5% to 27%) between 1996-2004 and 2010-2014 ( P = .016 and P < .001, respectively). The prevalence of positive sinus cultures increased from 40% to 85% between 1996-2004 and 2010-2014 ( P = .018). Patients with pulmonary MRSA were more likely to be coinfected with pulmonary P aeruginosa (risk ratio, 2.4; 95% CI, 1.2-4.8; P = .015) or Aspergillus fumigatus (risk ratio, 2.2; 95% CI, 1.2-4.8; P = .035). Conclusions: There is low to moderate correlation between pulmonary and sinus pathogens in CF patients. This is important to consider when treating infections. The prevalence of MRSA in sinus cultures has increased over time and warrants further investigation.